123 Use of The Induction Mobile Application in A Busy General Surgery Department. (4th May 2021) - Momin, S M B; Ismail, S
Abstract: Introduction: Contacting other hospital professionals, or accessing local guidelines is a common task for surgeons, which is usually facilitated by inefficient switchboard and intranet systems. Induction is a mobile application which includes crowd-sourced hospital directories and local guidelines, which could theoretically expedite these tasks. To assess this, we undertook a QIP within the General Surgery department using a bespoke Induction group. Method: A private Induction group was created with the features mentioned above. We audited Induction against local trust processes (Switchboard and Intranet Trust Guidelines). We estimated cost saving using the 2019 junior doctor pay-scales. We also surveyed our department to evaluate their experiences using the application with a Likert scale. Results: The timesaving from using Induction compared to current methods was on average 9.93 hours/week accumulated by 16 staff members, giving an estimated cost saving of £10, 636.54/year. In a qualitative analysis, respondents rated Induction 4.8/5 for speed and 3.4/5 for completeness of directory, compared to 1.5/5 and 4.5/5 respectively for switchboard. Regarding accessing clinical guidelines, respondents rated the app as 'easier' and 'quicker' than the intranet. Conclusions: We have demonstrated significant time and cost-savings using Induction compared to standard practices. Our QIP provides a replicable model to increase efficiency in surgery departments.